It's Payday on the S.S. Golden State - Unknown (Unknown)
This is the first year California Maritime Academy midshipmen have been paid the $65 which the boys In "white" are collecting from Lt. Hugh Severin, executlve officer second in command under Capt. Claude B. Mayo, in the top picture. In the picture below, Lt. (J. C.) J. F. Summeril and Cadet Chief Engineer John Donohue Inspect a Liberty party of 36 midshipmen who have just received their pay and are on their way to tour Stockton. Visitors may inspect the training ship Golden State any afternoon from 3 to 5 O'clock until it leaves Monday after its fourth visit there. A midshipman will escort visitors through the ship during those hours, and there is no military secrecy. Everything will be shown and explained.